Pengaruh Kecerdasan Spiritual, Penerapan Akuntansi, Pemahaman Perpajakan dan Peraturan Perpajakan Terhadap Kepatuhan Wajib Pajak OP UMKM - Tristianti Muzayana; Dirvi Surya Abbas; Indra Gunawan Siregar (STIKes Ibnu Sina Ajibarang, 2023)
Micro, Small and Medium Enterprises (MSMEs) are growing rapidly in fulfilling people's daily needs. MSMEs also participate in tax payments. According to the statement of the Directorate General of Taxes (DGT) that MSMEs have not maximally contributed to tax revenue. The success of this tax revenue effort is determined by several factors. This study aims to evaluate the factors that influence MSME taxpayer compliance. The results showed that spiritual intelligence and understanding of taxation did not have a significant influence on MSME taxpayer compliance. However, tax regulations have a significant influence on MSME taxpayer compliance.